Impact of antenatal depression on perinatal outcomes and postpartum depression in Korean women - Sae Kyung Choi; Yong Gyu Park; In Yang Park; Hyun Sun Ko; Jong Chul Shin (Journal of Research in Medical Sciences, 2014)
Background: Maternal prenatal mental health has been shown to be associated with adverse consequences for the mother and the child. However, studies considering the effect of prenatal depressive symptoms are lacking. The aim of this study was to examine the influence of antenatal depressive symptoms on obstetric outcomes and to determine associations between antenatal and postpartum depressions. Materials and Methods: This was a prospective cohort study. The Edinburgh postnatal depression scale (EPDS) questionnaire was completed by pregnant women receiving obstetrical care at Seoul St. Mary′s hospital in the third trimester of gestation. The electronic medical records were reviewed after delivery and perinatal outcomes were evaluated. The association between antenatal and postpartum depression was analyzed using the EPDS questionnaire, which was completed by the same women within 2 months of delivery. Results: Of the 467 participants, 26.34% (n = 123) had antenatal depressive symptoms, with EPDS scores of ≥10. There were no significant perinatal outcomes associated with antenatal depressive symptoms. During the postpartum period, 192 of the women in the initial study cohort were given the EPDS again as a follow-up. Of the 192 participants, 56 (29.17%) scored >10. Spearman correlation coefficient between the antenatal and postpartum EPDS scores was 0.604, which was statistically significant (P < 0.001). Conclusion: Antenatal depression does not lead to unfavorable perinatal outcomes. However, screening for antenatal depression may be helpful to identify women at risk of postpartum depression.